The MOBI-Kids Study Protocol: Challenges in Assessing Childhood and Adolescent Exposure to Electromagnetic Fields from Wireless Telecommunication Technologies and Possible Association with Brain Tumor Risk - Sadetzki, Siegal; Langer, Chelsea Eastman; Bruchim, Revital; Kundi, Michael; Merletti, Franco; Vermeulen, Roel; Kromhout, Hans; Lee, Ae-Kyoung; Maslanyj, Myron; Sim, Malcolm R.; Taki, Masao; Wiart, Joe; et al. (Frontiers in Public Health, 2014)
The rapid increase in mobile phone use in young people has generated concern about possible health effects of exposure to radiofrequency (RF), extremely low frequency (ELF) electromagnetic fields (EMF). MOBI-Kids, a multinational case-control study, investigates the potential effects of childhood and adolescent exposure to EMF from mobile communications technologies on brain tumor risk in 14 countries. The study, which aims to include approximately 1,000 brain tumor cases aged 10-24 years and two individually matched controls for each case, follows a common protocol and builds upon the methodological experience of the INTERPHONE study. The design and conduct of a study on EMF exposure and brain tumor risk in young people in a large number of countries is complex and poses methodological challenges. This manuscript discusses the design of MOBI-Kids and describes the challenges and approaches chosen to address them, including: 1) the choice of controls operated for suspected appendicitis, to reduce potential selection bias related to low response rates among population controls; 2) investigating a young study population spanning a relatively wide age-range. 3) conducting a large, multinational epidemiological study, while adhering to increasingly stricter ethics requirements; 4) investigating a rare and potentially fatal disease; and 5) assessing exposure to EMF from communication technologies. Our experience thus far developing and implementing the study protocol indicates that MOBI-Kids is feasible and will generate results that will contribute to the understanding of potential brain tumor risks associated with use of mobile phones and other wireless communications technologies among young people.